DOES THE TIMING OF EQUITY ISSUES INFORM CORPORATE POLICY? - Ratih, Dewi; Nuka Lantara, I Wayan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This study examines the timing of share issuances to meet corporate capital needs. The study uses specific data from share offering transactions in Indonesia for the period 2000-2020. This study provides an understanding of companies’ motivations for selling their shares, taking into account market timing in the dynamic stock markets of developing countries. The study’s findings have implications for capital market players, particularly potential investors, in understanding the information implied in the share prices offered by issuers at the time of issuance. The analysis reveals that companies offer larger shares when they are overvalued. Companies choose to offer shares when they are overvalued to maximize profits from the sale of their shares to meet their capital needs. Market timing considerations in share issuances are a share issuance policy that leverages investor perceptions in assessing market information. Companies intentionally offer shares when the share price is overvalued to profit from temporary pricing errors. The allocation of profits in these transactions reflects information about the company’s future policies. In general, the proceeds from these share sales are used by companies to increase capital for business development and, to some extent, to reduce corporate debt.